Proteksi Katodik Dengan Menggunakan Anoda Korban Pada Struktur Baja Karbon Dalam Larutan Natrium Klorida - Rahmat Ilham; Komalasari Komalasari; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pipe installation of oil and gas processing are located on land or at sea are generally made of carbon steel are susceptible to corrosion by the environment. A system to protect the corrosion of carbon steel is a sacrificial anode cathodic protection. Sample material used is low carbon steel with aluminum and zinc sacrificial anodes.Test condensation used is NaCl at a concentration of 500 ppm, 5.000 ppm, 15.000 ppm and 30.000 ppm then performed by varying the distance between the anode and cathode at a distance of 2 cm,3 cm and 4 cm. The results using the sacrificial anode aluminum and zinc. Where the best results in the sacrificial anode aluminum with carbon steel corrosion rate of 1,08 mpy for NaCl concentration of 500 ppm with the distance between electrodes 2 cm.Keywords: sacrificial anode, NaCl, corrosion rate, cathodik protection.